Christian Faith in a religiously Plural World - John Britto Chethimattam, (Journal of Dharma, 1978)
The book comprises the papers of a symposium which took place at the Washington & Lee University, Lexington, Virginia, U.S.A., April 22-24, 1976. The symposium consisted of two major papers by two Christian representatives and the responses given to them by participants from other Christian churches and other religious traditions.